Penggunaan Metode Job Safety Analysis untuk Mengurangi Risiko Kecelakaan Pekerjaan Ketinggian Penggantian Kabel Elevator Lift di PT. XYZ - Bima Putra Pratama; Akmal Suryadi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The purpose of the research conducted by the author is to evaluate how the Job Safety Analysis (JSA) method is used as a strategic step to find potential hazards and reduce the risk of work accidents at work at height, especially in the elevator lift cable replacement task at PT XYZ. JSA is used to analyze work steps, find hazards, and provide effective risk control solutions. This study shows that proper implementation of JSA can reduce work accidents by 40%, increase workers' awareness of risks, and create a safer work environment. This research uses a risk matrix to identify various risks classified by their likelihood and consequence levels. Qualitative analysis method was used in this study. The results show that most work activities have a high to very high level of risk, and the use of appropriate (PPE) and increased compliance with standard operating procedures (SOPs) are needed to control them. This research provides practical advice on how to reduce the risk of occupational accidents to employees at PT XYZ.